2023
DOI: 10.1186/s12879-023-08037-x
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in the homeless population: a scoping review and meta-analysis examining differences in prevalence, presentation, vaccine hesitancy and government response in the first year of the pandemic

Abstract: Aims People experiencing homelessness (PEH) have been identified as being increasingly susceptible to Coronavirus disease (COVID-19), with policies enacted to test, isolate, increase hygiene practices and prioritise vaccines among this population. Here, we conduct a scoping review of the current evidence-base pertaining to the prevalence and presentation of COVID-19 in PEH, COVID-vaccine hesitancy rates and government interventions enacted within the first year of the pandemic for PEH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 91 publications
1
3
0
Order By: Relevance
“…Similar findings were observed by enabling essential workers to get vaccinated in their place of work. These results also align with published articles (14,44). Still, our study also identified that the inadequate distribution of infrastructure across neighborhoods requires explicit attention to guarantee fair vaccine distribution more generally.…”
Section: We Made Sure (To Connect) With Friendship Centers Which Is W...supporting
confidence: 90%
See 1 more Smart Citation
“…Similar findings were observed by enabling essential workers to get vaccinated in their place of work. These results also align with published articles (14,44). Still, our study also identified that the inadequate distribution of infrastructure across neighborhoods requires explicit attention to guarantee fair vaccine distribution more generally.…”
Section: We Made Sure (To Connect) With Friendship Centers Which Is W...supporting
confidence: 90%
“…Another populationbased survey in Canada also identified that essential non-healthcare workers had lower intention to receive a COVID-19 vaccine than non-essential workers (12). Evidence from other studies from high-income countries also points to homelessness and disability influencing the acceptance of and access to COVID-19 vaccines (13)(14)(15).…”
Section: Introductionmentioning
confidence: 94%
“…In the present study, we found a high proportion of asymptomatic adults among the positive-COVID-19 participants who were homeless (42.7%). A recent meta-analysis reported a rate of 65% in the same population ( 48 ). These findings point to the need for broad and regular screening programs among the population experiencing homelessness to prevent clusters of infection in crowded or inadequate accommodations.…”
Section: Discussionmentioning
confidence: 99%
“…Even in our study, the incidence for SARS-CoV-2 infections was disproportionately higher than that reported for RSV and influenza, although these figures were reasonably inflated by the oversampling of HP during the early stages of the pandemic. The retrieved reports stress how rapidly a SARS-CoV-2 outbreak could spread across the homeless shelters and the need for raising and maintaining appropriate preventive and containment measures even in post-pandemic settings-for example, by achieving and maintaining high vaccination rates [137,138].…”
Section: Generalizabilitymentioning
confidence: 99%